Knowledge, attitude, and practice towards COVID-19 among university students in Indonesia: A cross-sectional study - Sulistyawati Sulistyawati; Syamsu Hidayat; Siwi Pramatama Mars Wijayanti; Tri Wahyuni Sukesi; Siti Kurnia Widi Hastuti; Surahma Asti Mulasari; Fatwa Tentama; Rokhmayanti Rokhmayanti; Ulinnuha Yudiansa Putra; Sitti Nur Djannah (International Journal of Public Health Science (IJPHS), 2021)
The presence of asymptomatic people exacerbates the widespread Coronavirus disease (COVID-19) transmission. The majority of them come from young people. This study aimed to explore the knowledge, attitude, and practice related to COVID-19 among university students in Indonesia, and the potential factor influenced their knowledge. A cross-sectional study involved 1,427 university students were carried out using an online survey from March 28 to April 10, 2020. A structured questionnaire consist of six sections focuses on knowledge, attitude, and preventive measure related to COVID-19 was used to collect the data. The analysis was performed using descriptive, Mann-Whitney, and Kruskal-Wallis tests. Results of the analysis indicated a significant difference in terms of mean between males and females regarding knowledge about preventing and protect others from COVID-19, the risk factor of getting COVID-19 infection, and knowledge that COVID-19 is curable. Knowledge total score among the respondent, there was a significant difference within the research group. This study demonstrates that the respondent has a basic knowledge about COVID-19 and the proper attitude, but it seems they are not consistent on practice in a particular measure.